Identification of sex- and inflammation-associated heterogeneity in the mouse omentum - Ding, Yi; Xiao, Shu-Yu; Wang, Jun-Jie; Ren, Zhi-Yi; Miao, Xiao-Cao; Ding, Xian-Ting; Xing, Xin; Li, Dong-Xue (Frontiers in Immunology, 2025)
The omentum is a critical intraperitoneal organ essential for peritoneal homeostasis, yet detailed characterization of its cellular composition remains limited by the lack of validated markers. Here, we employed single-cell RNA sequencing to systematically define cellular heterogeneity in naive and activated mouse omentum from both sexes. Our analysis identified previously uncharacterized immune and stromal cell subsets, including three macrophage subtypes with activation-dependent gene expression patterns, implying specialized roles in inflammation and immune regulation. Comparative analysis revealed marked transcriptional differences between omental and peritoneal macrophages, underscoring tissue-specific microenvironments. Additionally, sexually dimorphic gene expression in omental stromal cells correlated with peritoneal macrophage polarization, indicating sex-specific regulatory mechanisms. Critically, macrophages from omentum of female mice with ovarian cancer metastases showed unique gene signatures associated with tumor migration and invasion. Collectively, we provide the first comprehensive atlas of omental cell populations stratified by sex and activation state, offering novel insights into peritoneal immunity and identifying potential therapeutic targets for inflammatory and metastatic diseases.